A new mountain pitviper of the genus Ovophis Burger in Hoge amp; Romano-Hoge, 1981 (Serpentes, Viperidae) from Yunnan, China - Xian-Chun Qiu; Jin-Ze Wang; Zu-Yao Xia; Zhong-Wen Jiang; Yan Zeng; Nan Wang; Pi-Peng Li; Jing-Song Shi (ZooKeys, 2024)
Based on a molecular phylogenetic analysis and morphological comparison, a new species of mountain pitviper, Ovophis jenkinsi sp. nov., is described. The new species was collected in Yingjiang County, Yunnan Province, China. It can be distinguished from congeneric species by the following characters: (1) internasals in contact or separated by one small scale; (2) second supralabial entire and bordering the loreal pit; (3) dorsal scales in 23 (25)–21 (23, 25)–19 (17, 21) rows; (4) 134–142 ventrals; (5) 40–52 pairs of subcaudals; (6) third supralabial larger than fourth in all examined specimens of Ovophis jenkinsi sp. nov.; (7) deep orange-brown or dark brownish-grey markings on dorsal head surface; (8) background color of dorsal surface deep orange-brown or dark brownish-grey; (9) both sides of dorsum display dark brown trapezoidal patches; (10) scattered small white spots on dorsal surface of tail.